South Africa's construction of a developmental state? The case of the Gautrain mega-project - Doyle, Nicola Peta (My University, 2020)
This research report assesses how the South African state has employed public sector investment projects to achieve developmental goals, using phase one of the Gautrain mega-project (2000-2012) as a case study, and bearing the imminent development of phase two – named Gautrain Two – in mind, subject to approval by National Treasury. The study is framed from a developmental state perspective. It does not, however, take a traditional, industrial or trade policy approach to the developmental state. Rather, it updates the developmental state model to mean the formation of meaningful economic partnerships between different levels of the state and the private sector, and the provision of infrastructure that serves a public good. The Gautrain was built through a public-private partnership between the Gautrain Management Agency, a subsidiary agency of the Gauteng Provincial Government, and Bombela Concession Company. The study finds that, despite initial contestation surrounding exorbitant costs, social exclusion and construction impacts raised by political entities and civil society groups, the Gautrain project brought important economic and social benefits to the Gauteng city region. These include employment creation, land use and commercial benefits, contribution to gross domestic product and reduced greenhouse gas emissions. Further, the proposed expansion of the train network in Gautrain Two demonstrates the Gautrain’s aspiration to meet the transport demand of all social classes in Gauteng. The study concludes that the Gautrain is an example of a developmental state project led by a provincial arm of the South African state from which others can learn. The study employed qualitative research methods of document analysis and supplementary interviews.
A research report submitted to the Faculty of Humanities at the University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Arts in Development Studies, Johannesburg, June 2020.